Tyrosine Kinase Inhibitor Resistance Increased the Risk of Cerebral Radiation Necrosis After Stereotactic Radiosurgery in Brain Metastases of Non-small-Cell Lung Cancer: A Multi-Institutional Retrospective Case-Control Study - Zhuang, Hongqing; Tao, Liyuan; Wang, Xin; Shi, Siyu; Yuan, Zhiyong; Wang, Enmin; Chang, Joe Y. (Frontiers in Oncology, 2020)
Objective: To investigate the relationship between the timing of SRS intervention and the complications of cerebral radiation necrosis(CRN) in patients with brain metastases of lung adenocarcinoma who received TKI treatment. Methods: A total of 361 targets from 257 patients with brain oligo-metastases of lung adenocarcinoma who received Cyberknife treatment between 2010 and 2017 were retrospective collected from three Cyberknife centers. The difference in brain necrosis between patients with or without TKI application was statistically counted. Logistic regression analysis was used to analyze the effect of applying TKI on the occurrence of CRN in patients, and the effect of SRS before and after TKI resistance on CRN. Results: The rate of CRN in the TKI group was significantly higher than that in the non-TKI group. The incidence of brain necrosis in patients undergoing SRS after drug resistance was significantly higher than that in patients undergoing SRS before drug resistance. Regression analysis showed that combination of TKI with SRS, and SRS after TKI resistance were important influencing factors for CRN. Conclusion: Performing the SRS for brain metastases after TKI resistance worsened the occurrence of CRN of patients treated with TKI.